Simulation of radioecological processes by a method box models on an example of village in Volun of area - Матвєєва, І.В.; Заїтов, В.Р.; Кутлахмедов, Ю.О.; Ісаєнко, В.М.; Криворотько, В.М. (Proceedings of National Aviation University (archive), 2005)
The outcomes of flow analysis of radionuclides of Cs-137 in an ecosystem are reviewed village Galusiya and the chamber model given of ecosystem is built. It has allowed to evaluate patches of formation dose`s loadings of internal irradiation of miscellaneous groups of the population - working, retirees and children, and prognosing dynamics these of doses the subsequent years after accident and to evaluate ecological danger to the population.